British literature in transition, 1980-2000 : accelerated times - Pollard, Eileen; Schoene-Harwood, Berthold (Cambridge : Cambridge University Press, 2019)
The literature of twentieth-century Britain's final twenty years represents a crash course in transitional history. In the aftermath of the 1970s, the nation's hopes of becoming more efficient were high, leading to the fundamental domestic shake-up that was Margaret Thatcher's neoliberal revolution (1979-90). Following the end of the Cold War, Europe was undergoing radical rejuvenation, while the world as a whole began to thrive on new levels of connectivity and proximity brought through rapid advances in communication technology. Later, in the 1990s, Britons were asked to countenance not only internal devolution, but also the crystallisation of a brand-new European and global order. This volume shows how British literature recorded contemporaneous historical change. It traces the emergence and evolution of literary trends as well as enduring transitional shifts in genre, tone, style and thematic preoccupation.
Machine generated contents note: Introduction; Part I. Transitions: 1. The ends of postmodernism Peter Boxall; 2. Historical fiction and political regeneration Dougal Mcneill; 3. Strategies of survival in experimental poetry Luke Roberts; 4. Dramatic evolutions/bodily violations Nadine Holdsworth; 5. No such thing as society: the novel under neoliberalism Eileen Pollard and Berthold Schoene; Part II. Nation: 6. Black British writing: from gulags to ships Henghameh Saroukhani; 7. Working-class writing and the decline of class consciousness Nick Bentley; 8. Northern radical theatre and community performance Phil O'brien; 9. Pit closure as art: poetry from the North of England James Underwood; 10. The road to Tollund: Northern Ireland's literature of transformation Richard Kirkland; 11. Entangled (k)nots: reconceptualizing the nation in Scottish devolution writing Carla Sassi; Part III. Society: 12. Inter-feminism/s: women writing back to the future Diana Wallace; 13. The rise of ladlit and chicklit Imelda Whelehan; 14. A gay story, a history: gay male liberation and queer rumination Allan Johnson; 15. Searching for something: the post-secular faiths of British fiction Andrew Tate; 16. Dystopia and euphoria: time-space compression and the city Alexander Beaumont; Part IV. Acceleration: 17. Coded networks: literature and the information technology revolution Anna Mcfarlane; 18. Nature's history: environmentalism and the nature novel John Parham; 19. Like any other commodity? Literary prize culture, commercialization, and the rise of a new reading public Caroline Edwards; 20. Making sense of the world: literature and globalization Philip Leonard.
Title from publisher's bibliographic system (viewed on 11 Dec 2018).
Keywords: English literature -- 20th century -- History and criticism; Literature and society -- Great Britain -- History -- 20th century